Exercise preconditioning prevents left ventricular dysfunction and remodeling in monocrotaline-induced pulmonary hypertension - Schmidt, Cristine (2020)
Background: Despite pulmonary arterial hypertension (PAH) directly affects the right ventricle (RV), important structural, functional, and molecular changes also occur in left ventricle (LV). The objective of our study was to analyze the hypothetical cardioprotective effects of exercise preconditioning on LV in rats with monocrotaline (MCT)-induced PAH. Methods: Forty male Wistar rats were randomly separated in sedentary (SED) and trained group (EX; running sessions of 60 min/day, 5 days/wk, at 25 m/min, for 4 weeks). After 4 weeks, animals were injected with MCT (60 mg/kg; SED + MCT; EX + MCT) or vehicle (SED + V). Following an additional period of 4 weeks where all animals remained sedentary, we completed LV hemodynamic evaluation in baseline and isovolumic conditions and collected LV samples for histological and molecular analysis. Results: Preconditioning with exercise was capable to restore LV systolic and diastolic dysfunction in both baseline and isovolumic conditions (P < .05). This improved was paralleled with prevention of LV cardiomyocytes atrophy, fibrosis, and endothelin 1 mRNA levels (P < .05). Conclusions: Our findings suggest that exercise preconditioning can prevent LV dysfunction secondary to MCT-induced PAH, which is of particular interest for the familial form of the disease that is manifested by greater severity or earlier onset.